Towards Natural Engagement in Nonexhibitional Dramatic Role-Plays - Russell DiNapoli (Ibérica, 2003)
Modern language teaching and drama have long had a tenuous relationship. Foreign/second language teaching (F/SLT) and Language for Specific Purposes (LSP) instruction often mistakenly associate drama with learning games and role-play simulations. However, these remedial activities, though useful, offer only limited opportunities for natural speech interaction. This article argues that, as a natural dialogical process of cognitive and affective involvement, nonexhibitional dramatic role-play generates authentic meaning through action and personal commitment.